The Tragic Death of a Utah Goblin: Conservation and the Problem of Abiotic Nature. Issue 2 (3rd May 2020) - Lee, Alexander
ABSTRACT: Biocentric (life-centered) and ecocentric (ecosystem-centered) ethics offer a rich discourse on protecting biotic communities – defending conservation with inherent value tied to life. A problem arises from these views if mountains, glaciers, canyons, and other abiotic natural objects (often foci of conservation efforts) matter in and of themselves. Abiotic nature helps demonstrate and delineate the boundaries of environmental ethics grounded in life-based axiology. A series of thought experiments suggest that orienting conservation as a question of obligation offers an additional avenue to explore and defend the protection of abiotic nature; agreements and property rights plausibly ground moral obligations to conserve abiotic nature.